Claves epistemológicas sobre la seguridad: estructuras y posibilidades en las políticas públicas - Rivera Alfaro, Ronald (2015)
The successful conduct of security politics is determined by epistemological orientation that operationalized of state intervention in a polysemous world , with integration to the action of the local sectors, national and international part of the new treatment must take to counter the schemes of risks and threats, from there we put our attention on visualize the structure of the discurse on security that have been implemented in Costa Rican society through the adoption of its public policy on security.